THE ROLE OF CRITICAL THINKING IN ENGLISH LANGUAGE DEVELOPMENT (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Critical thinking is a vital component of English language development, especially in today’s dynamic educational landscape. This article explores the role of critical thinking in enhancing language comprehension, problem-solving abilities, and communication skills among learners. By engaging with English through a critical lens, students are better able to analyze texts, articulate their ideas, and become independent learners. The integration of critical thinking into English language education encourages deeper learning, enabling students to approach the language with a more analytical and reflective mindset. This article also discusses practical strategies for educators to incorporate critical thinking into their teaching practices, leading to more effective language acquisition and proficiency.